The Effect of Methanol Fractıonated of Luvunga sarmentosa on In Vıtro Sperm Membrane Integrıty - Permatasari, Silvani; Nuha, Alya Firyal; Ratnasari, Arini; Widayati, Ratna; Ka Praja, Rian (Medical Laboratory Technology Journal, 2024)
Infertility cases in the world are increasing in 2020, with 186 million individuals affected worldwide. The most common cause of male infertility is due to decreased sperm quality. Sperm membrane integrity is known to play an essential role in the fertilization ability of spermatozoa. The methanol fraction of Luvunga sarmentosa root extract has the highest antioxidant activity compared to other fractions and can improve sperm motility in vitro. This study aims to determine the effect of the methanol fraction of Luvunga sarmentosa root extract on human sperm membrane integrity and the effective concentration of Luvunga sarmentosa methanol extract fraction to improve sperm membrane integrity in vitro. The samples used were washed human spermatozoa in vitro, then added BWW medium, and incubated at 37℃ for 1 hour with methanol fraction of Luvunga sarmentosa root extract at concentrations of 100, 500, 1000, and 5000ng/ml as well as the control group (BWW only). Furthermore, 100uL of each sample was added to 1mL of Hypo-osmotic swelling (HOS) solution, then incubated at 37oC for 30 minutes to see the integrity of the spermatozoa membrane from the tail swelling. The results showed that sperm membrane integrity significantly increased at 100, 500, 1000, and 5000ng/mL concentrations compared to the control group. The methanol fraction of Luvunga sarmentosa root extract was most effective at a concentration of 100ng/mL. Methanol fraction of Luvunga sarmentosa root extract can improve human sperm membrane integrity.